Penerapan Konsep Taman Rakyat Pada Interior Pusat Seni Kriya Nusantara di Surabaya - Stella Tjoanda (Intra, 2014)
Design of Art & Craft Center in Surabaya Indonesia is means to introduce one of Indonesian art, which is Seni Kriya that is derived from all regions in Indonesia. This project is expected to attract the public to know what Seni Kriya  are, thus it will not be forgotten and be able to evolve as part of the creative industry in the international market. This design concept is "People's Park". Park means “a fun /entertaining place”, and people means “a population of a country ”, with the intent that this art & craft center will be a fun and entertaining means to the society. The concept implementation focusing on selection of natural materials, and space circulation that are connected to each other. The scope of this design include the Gallery as a major facility, the store / souvenir shop and workshops as a means of supporting.The gallery and workshop provides information and knowledge for visitors. Store facilities focusing on marketing, selling the craft products.